Fever-induced Brugada syndrome in a 9-year-old boy presenting with acute chest pain - Besli, Gülser Esen; Yıldırım, Sema; Akalın, İbrahim and Ayhan, Yusuf İzzet and Kısıoğlu, Merve and Berdeli, Afig (The Turkish Journal of Pediatrics, 2018)
Brugada syndrome, an arrhythmogenic disease, occurs due to mutations involving cardiac sodium channels. It is characterized by persistent or transient ST-segment elevation in the right precordial electrocardiogram leads that could be unmasked by several circumstances, with fever particularly. Molecular and cellular mechanisms leading to Brugada syndrome have not been completely elucidated. Mutations of the SCN5A gene encoding the pore-forming α-subunit of the cardiac sodium channel protein have been attributed in the molecular diagnosis. Although this syndrome is well-known in adults, it is less frequently reported in infants and children. We describe a 9-year-old Turkish boy with a family history of sudden cardiac death, who presented with chest pain and fever-induced expression of the Brugada syndrome phenotype that might be associated with a mutation in SCN5A gene.